Functional characteristics of left ventricular synchronization via right ventricular outflow-tract pacing detected by two-dimensional strain echocardiography - Yasutaka Hirayama, MD; Yuichiro Kawamura, MD, PhD; Nobuyuki Sato, MD, PhD; Tatsuya Saito, MD, PhD; Hideichi Tanaka, MD, PhD; Yasuaki Saijo, MD, PhD; Kenjiro Kikuchi, MD, PhD; Katsumi Ohori, MD, PhD; Naoyuki Hasebe, MD, PhD (Journal of Arrhythmia, 2017)
Background: Recently, due to the detrimental effects on the ventricular function associated with right ventricular apical (RVA) pacing, right ventricular septal (RVS) pacing has become the preferred pacing method. However, the term RVS pacing refers to both right ventricular outflow-tract (RVOT) and mid-septal (RVMS) pacing, leading to a misinterpretation of the results of clinical studies. The purpose of this study, therefore, was to elucidate the functional differences of RVA, RVOT, and RVMS pacing in patients with atrioventricular block. Methods: We compared the QRS duration, global longitudinal strain (GLS), and left ventricular (LV) synchronization parameters at the three pacing sites in 47 patients. The peak systolic strain (PSS) time delay between the earliest and latest segments among the 18 LV segments and standard deviation (SD) of the time to the PSS were also calculated for the 18 LV segments at each pacing site using two-dimensional (2D) strain echocardiography. Results: RVMS pacing was associated with a significantly shorter QRS duration compared with RVA and RVOT pacing (154.4±21.4 vs 186.5±19.9 and 171.1±21.5 ms, P<0.001). In contrast, RVOT pacing revealed a greater GLS (−14.69±4.92 vs −13.12±4.76 and −13.51±4.81%, P<0.001), shorter PSS time delay between the earliest and latest segments (236.0±87.9 vs 271.3±102.9 and 281.9±126.6%, P=0.007), and shorter SD of the time to the PSS (70.8±23.8 vs 82.7±30.8 and 81.5±33.7 ms, P=0.002) compared with RVA and RVMS pacing. Conclusions: These results suggest that the functional characteristics of RVOT pacing may be a more optimal pacing site than RVMS, regardless of the pacing QRS duration, in patients with atrioventricular conduction disorders.